STUDI KOMPARATIF PERTUMBUHAN RUMPUT MULATO PADA LAHAN PASCA TAMBANG YANG DIBERI PUPUK BERBEDA - Irwan, Muh.; M., Armayani (Jurnal Sains dan Teknologi Industri Peternakan, 2021)
To determine the effectiveness of the use of organic fertilizers on the growth rate of grass mulato (brachiaria hybrid cv mulato) which is planted on the soil after mining PT. Vale, bro. located in sorowako, East Luwu Regency, South Sulawesi Province. This Research was conducted using a completely randomized design (CRD) factorial (4 x 3) with 3 times replication for each treatment combination. Factor A as a type of fertilizer and Factor B as a cutting age. Experiments are 36 total units. The results showed that the plant height given liquid organic fertilizer was significantly higher (P <0.01) than the plant height rate in the post-mining soil which was given granular fertilizer. This difference occurs because liquid organic fertilizer is faster absorbed by plants than organic solid fertilizer (granules). Post-mining land which is used as a medium for mulato grass growth is actually not a barrier to use. The conclusion of this research is the use of organic fertilizers in the cultivation of grass mulato (Brachiaria hybrid cv. Mulato) on post-mining land gave a positive response. The use of organic liquid fertilizer provides the best response compared to the control and solid organic fertilizer (granule).